Oxidant mediated one-step complete conversion of multi-walled carbon nanotubes to graphene quantum dots and their bioactivity against mammalian and bacterial cells - Biswas, Anupam; Khandelwal, Puneet; Das, Raja; Salunke, Gayatri; Alam, Aftab; Ghorai, Suvankar; Chattopadhyay, Samit; Poddar, Pankaj (Journal of Materials Chemistry B, 2017)
It is essential for any antibacterial agent (for clinical applications) that it should have high and selective toxicity towards bacterial cells only, and should not affect the human cells at the concentration used. Graphene quantum dots (GQDs) have emerged as a potential candidate for biomedical applications. However, a simple, low cost, safe, easy to execute, one-step synthesis of uniform and monodispersed GQDs with selective toxicity towards bacterial cells rather than mammalian cells is difficult to achieve. Herein, we have reported a one-step, low-cost, aqueous-phase, simple approach for the complete conversion of multi-walled carbon nanotubes into water-dispersible GQDs with an average size of similar to 3 nm using sodium bismuthate (NaBiO3) as a strong oxidant. The cyclic voltammetry and X-ray photoelectron spectroscopy results indicated that the as-synthesized GQDs suspension possess almost negligible amounts of metallic impurities. The cytotoxicity studies of GQDs against mammalian NIH 3T3 (mouse embryo fibroblast cells) and HEK 293T (human embryonic kidney cells) cells showed that the as-synthesized GQDs were non-cytotoxic up to the concentration of similar to 200 mu g mL(-1). The antimicrobial study shows that the synthesized GQDs have high and selective toxicity towards bacterial cells with a minimum inhibitory concentration of similar to 256 mu g mL(-1) for E. coli and B. subtilis and similar to 512 mu g mL(-1) for P. aeruginosa and S. aureus. The scanning electron microscopy and atomic force microscopy images show extensive cell damage via the perturbation of bacterial cell walls, which was consistent with the enhancement of reactive oxygen species production by almost two times in the bacterial cells upon incubation with similar to 256 mu g mL(-1) GQDs. Our study suggested that the as-synthesized GQDs can be used as a potential candidate for clinical applications as they possess high toxicity to bacterial cells and low toxicity to mammalian cells.

Antimicrobial synergy of silver-platinum nanohybrids with antibiotics - Ranpariya, Bansi; Salunke, Gayatri; Karmakar, Srikanta; Babiya, Kaushik; Sutar, Santosh; Kadoo, Narendra; Kumbhakar, Pathik; Ghosh, Sougata (Frontiers in Microbiology, 2021)
Various bacterial pathogens are responsible for nosocomial infections resulting in critical pathophysiological conditions, mortality, and morbidity. Most of the bacterial infections are associated with biofilm formation, which is resistant to the available antimicrobial drugs. As a result, novel bactericidal agents need to be fabricated, which can effectively combat the biofilm-associated bacterial infections. Herein, for the first time we report the antimicrobial and antibiofilm properties of silver-platinum nanohybrids (AgPtNHs), silver nanoparticles (AgNPs), and platinum nanoparticles (PtNPs) against Escherichia coli, Pseudomonas aeruginosa, and Staphylococcus aureus. The AgPtNHs were synthesized by a green route using Dioscorea bulbifera tuber extract at 100 degrees C for 5 h. The AgPtNHs ranged in size from 20 to 80 nm, with an average of similar to 59 nm. AgNPs, PtNPs, and AgPtNHs showed a zeta potential of -14.46, -1.09, and -11.39 mV, respectively. High antimicrobial activity was observed against P. aeruginosa and S. aureus and AgPtNHs exhibited potent antimicrobial synergy in combination with antibiotics such as streptomycin, rifampicin, chloramphenicol, novobiocin, and ampicillin up to variable degrees. Interestingly, AgPtNHs could inhibit bacterial biofilm formation significantly. Hence, co-administration of AgPtNHs and antibiotics may serve as a powerful strategy to treat bacterial infections.
Keywords: antibiofilm; antimicrobial synergy; biogenic synthesis; Characterization; silver-platinum nanohybrids

Catechin-capped silver-doped titanium dioxide nanoparticle enhanced photocatalytic toxic dye degradation - Ghosh, Sougata; Imboon, Tanawat; Layek, Rashbihari; Salunke, Gayatri; Parihar, Vijay Singh; Khumphon, Jeerawan; Webster, Thomas J.; Sutar, Santosh; Kityakarn, Sutasinne; Issro, Chaisak; Khamboonrueang, Dusadee; Thongmee, Sirikanjana (Frontiers in Chemistry, 2025)
Doping-associated surface modification is a powerful strategy to enhance the photocatalytic potential of n-type semiconductor nanomaterials. Silver (Ag) is one of the most effective dopants that can result in the retardation of the electron hole recombination-generating Schottky barrier at the TiO2 interface with a simultaneous extension of absorption to the visible region. This work presents a study on the effect of catechin, a bioactive principle polyphenol compound found in various plants, on the synthesis, Ag-doping and stabilization of TiO2 nanoparticles (TiO2NPs). The nanoparticles were irregular in shape with sizes ranging from 19 to 30 nm. Ag-TiO2NPs were fabricated using TiO2 as a precursor and 1%, 3%, and 5% AgNO3 as a doping agent. The average particle size of 1%Ag-TiO2NPs, 3%Ag-TiO2NPs, and 5%Ag-TiO2NPs was 27.3 +/- 7.5 nm, 29.8 +/- 9.6 nm, and 25.0 +/- 9.0 nm, respectively. High-resolution transmission electron microscopy (HRTEM) showed lattice fringes with an interplanar spacing of 0.23 nm corresponding to the Ag (111) plane in addition to the presence of the anatase phase of TiO2. Fourier transform infrared (FTIR) spectra exhibited a broad peak around 400-800 cm-1 that was attributed to Ti-O-Ti stretching vibrations which was slightly shifted in Ag-TiO2NPs due to changes in the local bonding environment around Ti atoms caused by interactions with Ag. Catechin loading in the TiO2NPs and Ag-TiO2NPs was between 1.55 and 3.3 wt. %. TiO2NPs, 1%Ag-TiO2NPs, 3%Ag-TiO2NPs, and 5%Ag-TiO2NPs exhibited superior photocatalytic degradation of methylene blue dye up to 78%, 87%, 91%, and 92%, respectively, and RhB dye up to 92%, 94%, 97% and 99%, respectively, with a pseudo-first-order reaction kinetics. Furthermore, its recyclability was also demonstrated for three cycles. The simplicity of fabrication and superior photocatalytic performance of TiO2 demonstrated here make this green route advantageous for environmental applications to treat dye contaminated effluent as well as for numerous other applications.
Keywords: catechin; green synthesis; methylene blue dye; Photocatalysis; Rhodamine B; silver doping; titanium dioxide nanoparticles

Molecular insights into the oleic acid accumulation in safflower - Salunke, Gayatri; Badhe, Yogesh; Singh, Vrijendra; Ghorpade, Prakash; Hegde, Mahabaleshwar; Kadoo, Narendra (Journal of the American Oil Chemists Society, 2025)
Most of the Indian safflower (Carthamus tinctorius L.) varieties produce oil rich in linoleic acid (LA, similar to 75%) and low in oleic acid (OA, similar to 15%). In the fatty acid biosynthetic pathway, the fatty acid desaturase 2 (FAD2) enzyme converts OA to LA. Safflower is reported to have 12-20 FAD2 genes. Gene expression analysis of four FAD2 genes during seed development in a high LA variety, PBNS-12, revealed high expression of FAD2-1 at 21 days after flowering (DAF), correlating with high LA accumulation. Fatty acid profiling of 448 Indian safflower germplasm accessions revealed four lines to have high (58%-77%) OA content, with NASF-39 having the highest OA content. Interestingly, all four high OA lines showed the same mutation in the FAD2-1 gene. The DNA sequence of FAD2-1 from the four high OA lines showed a deletion of C at the +606 position, resulting in a premature stop codon at the +733 position and a truncated protein of 244 amino acids. Hence, despite the high expression levels of FAD2-1 in NASF-39 at 18-21 DAF, it exhibited high OA (77%). The dysfunctional nature of the truncated FAD2-1 in NASF-39 was evident in molecular docking studies with 1-stearoyl-2-oleoyl phosphatidylcholine. We also sequenced FATB, a thioesterase responsible for releasing stearic acid from acyl carrier protein for further desaturation to oleic acid, where an A773G substitution was observed. This resulted in E258G substitution in NASF-39 FATB compared to that of PBNS-12. This probably made the acyl-binding pocket of NASF-39 FATB unstable, contributing to high OA accumulation. Thus, the outcomes of this study can help develop super and ultra-high oleic safflower varieties through various genetics and genomics approaches.
Keywords: Carthamus tinctorius; FAD2; FATB; Fatty acid desaturase; fatty acid thioesterase; linoleic acid